Early and late outcomes after trans-catheter aortic valve implantation in patients with previous chest radiation. Issue 13 (23rd February 2016) - Bouleti, Claire; Amsallem, Myriam; Touati, Aziza; Himbert, Dominique; Iung, Bernard; Alos, Benjamin; Brochet, Eric; Urena, Marina; Ghodbane, Walid; Ou, Phalla; Dilly, Marie-Pierre; Nataf, Patrick; et al.
Abstract : Objective: Surgery for aortic stenosis in patients with thoracic radiation therapy is associated with high morbi-mortality. Trans-catheter aortic valve implantation (TAVI) represents an alternative but has never been studied in this population. We aimed to compare outcomes in radiation and matched control patients undergoing TAVI and to identify predictive factors of survival. Methods: Between 2006 and 2011, 288 consecutive patients underwent TAVI in our institution, of whom 26 had previous chest radiation. They were matched 1:1 for age, sex and TAVI approach with controls. Results: In both groups, median age was 73 years, 50% of patients were male and 15% had a transapical approach. Procedural success was 88% in the radiation group versus 100% in controls (p<0.001) and 30-day survival was 92% in both groups. Five-year survival was 33%±10% in the radiation group and 42%±11% in controls (p=0.26). In radiation patients, the main cause of death was respiratory insufficiency in 40%. We identified four independent predictive factors of death in the radiation group: extracardiac arteriopathy (p=0.002) and the absence of β-blocker therapy (p=0.005) as preprocedural variables, and infectious complications (p=0.009) and a higher peak creatinine level (p=0.009) as postprocedural variables. In the radiation group, 89% of survivors were in New York Heart Association class I–II at last follow-up. Conclusions: Patients in the radiation group displayed high mortality rates although not significantly different from the controls. Respiratory failure was the main cause of death, emphasising the need for a careful pulmonary evaluation. Finally, we show a sustained improvement in functional results after TAVI in this population.